Method for preparing porous high-purity silicon material from photovoltaic waste silicon
Through the reaction alloying and nitriding of photovoltaic waste silicon with magnesium powder, combined with acid washing to remove impurities, the problems of low impurity removal rate and complex process in the purification process of photovoltaic waste silicon are solved, and high-purity and low-cost mass production is achieved and simplified processes, suitable for the preparation of porous structural materials.
Patent Information
- Application Number
- CN202411365977.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-20
Smart Images

Figure CN119160898A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicon materials, and in particular relates to a method for preparing porous high-purity silicon material from photovoltaic waste silicon. Background Art
[0002] As a renewable energy source, solar energy is environmentally sustainable and is an ideal choice for coping with energy shortages and environmental pollution. More than 94% of solar cells in the photovoltaic (PV) industry are crystalline silicon solar cells because of their low cost and high stability. This type of solar cell requires silicon wafers as substrate materials. The diamond wire saw process is the main slicing method used in the production of photovoltaic silicon wafers because of its high slicing efficiency and low saw damage layer. However, during the sawing process, due to technical limitations, about 30-40% of solar-grade silicon is wasted. These solid wastes may cause environmental pollution and may pose safety hazards if not handled properly. Therefore, the recycling of photovoltaic waste silicon has economic value and social significance.
[0003] Acid leaching is one of the most effective methods recognized by the photovoltaic industry to remove most metal impurities such as Fe, Al, Ni, Ca, Mg, etc. Although most of the metal impurities have been removed, a certain amount of impurities still remain after leaching. Moreover, a large amount of acid washing will cause serious pollution to the environment and the purification rate is not high. Therefore, some people have proposed a composite process combining acid leaching, calcination and deoxidation to remove metal impurities from the slit waste slag; ultrasonic aerosol spray drying method to obtain nano-scale silicon particles from silicon sludge waste slag; Si-Al alloying process, which can separate Si and SiC from the slit loss Si waste, fully mix with aluminum powder in a quartz crucible, and heat for 1 hour under argon at 1773K to obtain Al-Si ingot phase; electromagnetic force assisted slag treatment is to separate and purify silicon from the slit loss silicon waste slag; electromagnetic induction melting is to use electromagnetic force to remove non-metallic impurities or inclusions from molten alloys or metals; there are also plasma refining technology, vacuum melting method, carbon thermal reduction process and other methods to purify silicon from photovoltaic waste silicon; or directly conduct high-energy ball milling of photovoltaic waste silicon with materials such as carbon nanotubes to directly obtain silicon negative electrode materials. These methods have many problems, such as low impurity removal rate; too long process flow; too high process energy consumption; introduction of other impurities, repeated impurity removal reduces efficiency; too low purification yield, etc. Therefore, it is crucial to design a purification method with short process, high impurity removal rate, high yield and mass production capability.
[0004] In the prior art, Chinese patent CN102388121B discloses a method for separating and recovering silicon particles from silicon sawdust, wherein at least a portion of a lubricating fluid is separated from a solid particle mixture; the solid particle mixture is cleaned with an acid solution, in which the silicon particles are substantially insoluble and the metal particles and oxide particles are soluble, the metal particles and oxide particles are dissolved from the solid particle mixture, the acid solution is capable of generating flotation foam with the solid particle mixture, the foam comprising the silicon particles and abrasive particles; the cleaned solid particle mixture is collected, the cleaned mixture comprising silicon particles and abrasive particles; and the silicon particles in the cleaned solid particle mixture are separated from the abrasive particles by applying a density-dependent separation technique to the foam, the density-dependent separation technique being selected from sedimentation centrifugation, filtration centrifugation and hydrocyclone separation, and, before the density-dependent separation, the silicon particles are contacted with an iodine source to convert at least a portion of the silicon present therein into silicon iodide, wherein the separated silicon particles have a carbon content of less than 50 ppma and a metal contaminant content of less than 150 ppma. However, the process of this patent is too complicated, and the silicon material obtained needs further processing.
[0005] Chinese patent CN109052407A discloses a method for recycling and purifying silicon cutting waste, wherein the silicon waste slurry generated during the silicon ingot cutting process is subjected to solid-liquid separation and dried to obtain solid silicon waste; CaO, SiO2, and flux are mixed evenly to obtain a slag-forming agent; the slag-forming agent and solid silicon waste are mixed evenly, and placed in a medium frequency induction furnace, vacuumed and then introduced with argon gas, heated to a temperature of 1450-1700°C under argon atmosphere conditions, and smelted at a constant temperature for 0.5-4h, and cooled with the furnace to obtain a fused block; the silicon slag of the fused block is separated by diamond wire cutting to obtain high-purity silicon; the silicon cutting waste is subjected to induction furnace slag refining treatment using the full pyrometallurgical process, and separation and purification are placed in the same operation step, thereby realizing the comprehensive recovery and purification of silicon-containing waste during the silicon ingot cutting process. However, the process method of this patent requires too high a temperature and is complicated, and the energy consumption is too high and has certain dangers.
[0006] Chinese patent CN114655959A discloses a high-purity micro-nano silicon powder purified from photovoltaic industry silicon waste, and its purification method and application. The purification method uses photovoltaic silicon waste as raw material, and can volatilize the polymer in the silicon waste through high-temperature calcination. It can remove trace metal impurities through acid washing and drying, and reduce the carbon content and oxygen content in the photovoltaic silicon waste, thereby obtaining high-purity micro-nano silicon powder. However, the process method of the patent does not mention the removal of metal impurities in photovoltaic silicon waste, and only simply removes the silicon dioxide shell layer.
[0007] Chinese patent CN102642835A discloses a method for recovering silicon material from waste material generated by diamond wire cutting of crystalline silicon, wherein the collected waste material is passed into a centrifuge for centrifugation and sedimentation to obtain silicon material precipitate; the silicon material precipitate is solid-phase rinsed to remove impurities such as organic matter in the residual liquid in the solid and part of the diamond powder to obtain silicon powder of a certain purity; the solid-phase silicon powder is first washed with hydrochloric acid to remove metal impurities; the silicon powder pickled with hydrochloric acid is rinsed with pure water and then rinsed with hydrofluoric acid to remove oxides on the surface of the silicon powder; the silicon material rinsed with hydrofluoric acid is ultrasonically rinsed and dried; the dried silicon powder is purified by directional solidification ingot casting to obtain solar-grade silicon material; finally, the silicon material is crushed, pickled, rinsed, dried and then packaged. Although the process method of this patent has a low cost, its impurity removal rate is not high and further purification and processing is required.
[0008] The document "Removal of metal impurities from diamond wire saw silicon powder by vacuum electromagnetic directional solidification" (DOl: 10.1016 / j.vacuum.2023.112948) reports a purification method, which uses a high-frequency electromagnetic furnace to fill the dried raw powder material in a dense graphite crucible with a purity of 5n; in the high-frequency electromagnetic furnace, induction melting with vacuum liquid level change was first carried out; in order to prevent silicon powder from oxidizing during the experiment, the air in the furnace was first evacuated with a vacuum pump before injecting high-purity argon; during the melting process, the vacuum range was 600-500Pa and 90-10Pa, the overheating temperature was 1793K, and the temperature in the middle of the crucible wall was measured with a thermocouple pyrometer. Vacuum refining and directional solidification were studied in a high-frequency induction furnace. First, maintain a pressure of 90-10Pa, refine at 1793K for 4h, cool to 873K at a rate of 57K / min, and then cool naturally. When the temperature is lower than 323K, the furnace is continuously filled with high-purity argon. After the pressure rises to normal pressure, the sample is taken out. For the latter, the atmospheric pressure of the electromagnetic induction heating furnace is the same as the former. In addition to the purification method and heating method, the sample is first kept at 1793K for 30 minutes and then naturally cooled into bulk Si. Finally, the silicon ingot is heated for 1h to ensure that the silicon crystal is completely melted, and then the sample moves downward evenly at a predetermined rate. When the sample is taken out of the electromagnetic induction coil of the induction furnace, the same cooling method as vacuum refining is adopted. The method of this document has limited removal of solid-soluble impurities such as Al and Ga. Summary of the invention
[0009] In view of the deficiencies of the above-mentioned prior art, the present invention provides a method for preparing high-purity porous silicon material from photovoltaic waste silicon, solves the environmental pollution and resource waste caused by the accumulation of a large amount of photovoltaic waste silicon, and realizes controllable, low-cost, large-scale, high-purity silicon material preparation. The specific technical scheme is as follows:
[0010] The first object of the present invention is to provide a method for preparing high-purity porous silicon material from photovoltaic waste silicon, comprising the following steps:
[0011] Step 1: reacting silicon powder crushed from photovoltaic waste silicon with magnesium powder to synthesize magnesium silicide;
[0012] Step 2: Grinding magnesium silicide to obtain magnesium silicide powder;
[0013] Step 3: subjecting the ground magnesium silicide powder to a nitridation reaction treatment;
[0014] Step 4: The product obtained by the nitridation reaction is acid-washed, filtered, and dried to obtain a high-purity porous silicon material.
[0015] The present invention uses photovoltaic waste silicon as raw material, removes most of the metal and non-metal impurities in the alloying, nitriding and pickling processes, and obtains a high-performance porous silicon material with high purity, very few impurities such as B and P, large porosity, and can be directly used through simple processing.
[0016] The preparation process of the present invention is simple. When Mg3N2 is removed by pickling, Si and pore space are left, so that the interior of the obtained silicon material is full of holes, and a three-dimensional porous structure material with good morphology is obtained, so that most of the metal and non-metal impurities are exposed, and the removal of impurities in the pickling process is strengthened, so that the pickling impurity removal efficiency is greatly improved, and the problem that only impurities on the surface of the material can be removed during the pickling process is solved; at the same time, space is reserved for the volume expansion caused by silicon charging and discharging, and the expansion of silicon in the process of lithium insertion and de-lithiation is effectively alleviated, and material pulverization is avoided. The porous structure has obvious advantages in alleviating the expansion of battery materials, and the application in lithium-ion batteries has long-term cycle and excellent rate performance.
[0017] The size of the porous silicon material (particles) prepared by the present invention is 2-8 μm. The control of the particle size enables the battery negative electrode material made of the porous silicon to have a high capacity while also obtaining a high capacity retention rate. It can be used as a raw material of silicon such as solar grade, has a good commercial application prospect, realizes the purification and reuse of photovoltaic waste silicon, and achieves the purpose of integrating resources and reducing pollution.
[0018] Furthermore, in the step 1, the particle size of the silicon powder crushed from the photovoltaic waste silicon is 1-10 μm, and the mass ratio of silicon powder to magnesium powder is 1:(1-2).
[0019] Furthermore, in step 1, the reaction conditions of the silicon powder and magnesium powder are heating to 550-600° C. under a protective gas atmosphere and reacting for 4-6 hours.
[0020] The starting temperature of the alloying reaction of silicon powder and magnesium powder in the present invention is 500°C. When the reaction temperature is lower than 500°C, Mg2Si will not be formed. When the reaction temperature is higher than 600°C, magnesium is easily evaporated, resulting in magnesium loss, causing some silicon particles to not undergo alloying reaction with magnesium.
[0021] Furthermore, in step 1, the heating rate is 2-10°C / min.
[0022] Furthermore, in step 2, the particle size of the ground magnesium silicide powder is 3-5 μm.
[0023] Furthermore, in step 2, the preparation method of the magnesium silicide powder is as follows: the magnesium silicide synthesized in step 1 is placed in a ball mill, n-hexane is used as a grinding aid, 8-12 times the mass of zirconium oxide ball milling beads are added, and the ball milling is carried out at 300-500r / min for 3-5h; the ball-milled powder is subjected to ultrasonic oscillation for 0.5-2h using ethanol as a dispersant, and then centrifuged at 300-500r / min for 5-10min to obtain the supernatant, the obtained supernatant is centrifuged at 600-800r / min for 5-10min, and the lower layer of precipitate is removed, and the precipitate is freeze-dried to obtain magnesium silicide powder.
[0024] Furthermore, the nitridation reaction treatment in step 3 is to heat the ground magnesium silicide powder to 700-900° C. at a heating rate of 2-10° C. / min in an atmosphere containing ammonia and keep the temperature for 3-6 hours.
[0025] The minimum temperature for the nitridation reaction to occur is 700°C, and the nitridation temperature cannot exceed 900°C, otherwise a by-product MgSiN2 will be produced; and the reaction temperature of the present invention is relatively low, which is more environmentally friendly and safer.
[0026] Furthermore, the product obtained by the nitridation reaction treatment in step 4 is pickled with a 0.5-1.5 M / L hydrochloric acid solution for 3-5 hours.
[0027] The beneficial effects of the present invention are:
[0028] 1. The present invention uses photovoltaic waste silicon as raw material combined with gas phase dealloying and pickling to prepare a porous structure silicon material with excellent electrochemical properties. This method does not involve a template, is simple and efficient to operate, has a short process cycle, and the raw materials are cheap and widely available, and is easy to mass produce.
[0029] 2. The silicon dioxide shell layer of photovoltaic waste silicon used in the present invention can also form porous structure silicon through gas phase dealloying, which improves the raw material utilization rate and eliminates the step of removing silicon dioxide separately, saving time and economic costs. It is economical, green and environmentally friendly, and is in line with the national green energy-saving policy trend.
[0030] 3. The preparation method of the present invention can also efficiently remove trace impurities contained in the silicon dioxide shell layer of photovoltaic waste silicon in a series of reactions, reduce side reactions when preparing electrode negative materials, improve the capacity and capacity retention rate of the battery, and can also perform carbon coating and other operations to further enhance the electrochemical performance, and has broad application prospects.
[0031] 4. The porous structure prepared by the present invention not only strengthens the removal of solid-soluble impurities during the pickling process, with a high impurity removal rate, but also reserves space for the volume expansion caused by silicon charging and discharging, effectively avoiding material pulverization. The porous structure has obvious advantages in alleviating the expansion of battery materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a process flow chart of the present invention;
[0033] Figure 2 1 is an XRD analysis diagram of each reaction product in Example 1 of the present invention;
[0034] Figure 3 The electron microscope images of the porous silicon materials in Example 1 and Comparative Example 1 of the present invention are shown;
[0035] a-Example 1, b-Comparative Example 2;
[0036] Figure 4 This is a schematic diagram of the cycle performance test of the porous silicon material in Example 1 of the present invention;
[0037] Figure 5 This is a schematic diagram of rate performance testing of the porous Si obtained in Example 1 of the present invention at different current densities;
[0038] Figure 6 This is a bar chart comparing the impurity content before and after purification in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0040] Embodiment 1:
[0041] like Figure 1 As shown, a method for preparing high-purity porous silicon material from photovoltaic waste silicon comprises the following steps:
[0042] Step 1: The photovoltaic waste silicon is crushed to control the size to 1-10 μm, and the photovoltaic waste silicon and 200-mesh magnesium powder are uniformly mixed in a V-type mixer at a molar ratio of 1:1.75 and placed in a stainless steel container, and then heated to 550°C in an argon-protected tubular furnace for 4 hours to obtain a silicon-magnesium alloy;
[0043] Step 2: placing the obtained silicon-magnesium alloy in a ball mill, adding zirconium oxide ball milling beads as required, using n-hexane as a grinding aid, ball milling at a speed of 400 r / min for 4 hours, using ethanol as a dispersant for the ball-milled magnesium silicide powder, ultrasonically oscillating for 1 hour, centrifuging the obtained solution in a centrifuge at a speed of 400 r / min, taking the supernatant, and removing the precipitate with a larger particle size; centrifuging the supernatant in a centrifuge at a speed of 700 r / min, taking the precipitate, removing the supernatant with a smaller particle size, and freeze-drying the precipitate for 12 hours to obtain magnesium silicide with a particle size of 3-5 μm;
[0044] Step 3: The obtained Mg2Si powder is heated to 780°C at a heating rate of 5°C / min in an ammonia atmosphere and kept at this temperature for 5 hours to carry out a nitridation reaction of magnesium silicide, and the magnesium silicide is nitrided to form Si and Mg3N2;
[0045] Step 4: The powder obtained after the nitridation reaction was pickled with 1M / L HCl solution for 4 hours to remove impurities such as Mg3N2, and then the solution was filtered to neutrality and freeze-dried for 12 hours to obtain a porous silicon material.
[0046] Experimental results:
[0047] Using X-ray diffraction technology, the XRD patterns of the reaction products in each process are obtained. Figure 2 From the XRD spectrum, it can be seen that Mg and Si completely react after high-temperature alloying to generate Mg2Si. After Mg2Si is nitrided in an ammonia atmosphere, Mg3N2 and Si are generated. Subsequently, Mg3N2 is removed by hydrochloric acid washing to remove impurities, leaving a three-dimensional porous structure Si.
[0048] The morphology of the synthesized material was observed by scanning electron microscopy. Figure 3 The SEM image of a clearly shows that the material synthesized in this way has uniform particle morphology, and the average particle size is 3-5μm; the material has a typical porous structure. If the material particle size is small, the tap density will be low, and if the particle size is too large, it will affect the material performance and the reaction kinetics during the dealloying process.
[0049] like Figure 4 This is a schematic diagram of the cycle performance test of the porous silicon material in Example 1 of the present invention. It can be seen that the porous silicon material of the present invention has a cycle performance of 1A·g -1 The long cycle test under current, the first three cycles were activated by a low current of 0.1C. The results showed that the porous silicon-1 The capacity is as high as 2018.56 mAh / g when cycled 100 times at a current density of . Figure 5 The schematic diagram of the rate performance test of the porous Si obtained in Example 1 at different current densities is shown in FIG. -1 Increase to 1A·g -1 , the capacity retention rate is still about 55% under the condition of 10 times current increase. -1 When the current is restored to 0.1A·g -1 When the battery is charged, the capacity is restored to about 2000mAh / g.
[0050] The comparison of impurity contents before and after purification in Example 1 of the present invention is shown in Table 1:
[0051] Table 1 Comparison of impurity contents before and after purification in Example 1
[0052]
[0053] As shown in Table 1, it can be seen that the preparation method of the present invention has an extremely obvious effect on the removal of impurities. The silicon dioxide impurity with the highest content is completely removed with the alloying and dealloying reactions, and most of the remaining trace impurities are also removed. The impurity content before and after purification is presented in a bar graph, as shown in FIG. Figure 6 It can be seen that a large number of impurities have been removed, among which the removal rate of many impurities is extremely high, and the removal rate of a small amount of impurities is lower, but there is also an obvious removal effect. The purity of the purified silicon has reached the 3N level. Direct use as an electrode material can effectively reduce the occurrence of side reactions and improve battery performance; it also provides a raw material basis for 4-9N high-purity silicon.
[0054] The porous silicon material obtained in Example 1 of the present invention leaves enough space to alleviate the volume expansion of silicon, effectively avoiding material pulverization. Compared with ordinary silicon-based negative electrode materials, its electrochemical properties, such as capacity, capacity retention rate, long cycle performance, rate, etc., are greatly improved.
[0055] Comparative Example 1:
[0056] A method for preparing silicon material from photovoltaic waste silicon comprises the following steps:
[0057] Step 1: The photovoltaic waste silicon is ball-milled to control the size to 1-10 μm, the photovoltaic waste silicon and magnesium powder are uniformly mixed in a V-type mixer at a mass ratio of 1:1.75 and placed in a container, and then heated to 500°C in an argon-protected tubular furnace for 6 hours to obtain a silicon-magnesium alloy;
[0058] Step 2: ball-milling the obtained silicon-magnesium alloy, centrifuging it, vacuum filtering it, and freeze-drying it to obtain magnesium silicide powder with an average particle size of 3-5 μm;
[0059] Step 3: The obtained Mg2Si powder of suitable particle size is placed in an NH3 atmosphere with a small amount of argon as protective gas, and the temperature is increased to 780°C at a rate of 5°C / min and then kept at this temperature for 6 hours;
[0060] Step 4: The powder obtained after nitridation was acid-washed with 1M / L HCl solution for 4 hours to remove Mg3N2 impurities, and then the solution was filtered to neutrality and freeze-dried for 12 hours to obtain silicon material.
[0061] If the alloying temperature is too low during the reaction, the alloying reaction between silicon powder and magnesium powder will be insufficient. If the silicon-magnesium alloy obtained shows that silicon is not completely reacted, it will cause particle agglomeration. If silicon powder and magnesium powder cannot completely react to synthesize silicon-magnesium alloy, it will not be possible to prepare porous silicon with excellent morphology. Figure 3 b. During the pickling process, the impurities inside the silicon of this structure cannot be completely exposed, which reduces the impurity removal rate and leads to low silicon purity. In addition, this structure makes it difficult to alleviate the volume expansion of silicon during the lithium insertion and extraction process, which reduces its electrochemical performance.
[0062] Comparative Example 2:
[0063] A method for preparing silicon material from photovoltaic waste silicon comprises the following steps:
[0064] Step 1: The photovoltaic waste silicon is ball-milled to control the size to 1-10 μm, and the photovoltaic waste silicon and magnesium powder are uniformly mixed in a V-type mixer at a mass ratio of 1:1.75 and placed in a container, and then heated to 550°C in an argon-protected tubular furnace for 4 hours to obtain a silicon-magnesium alloy;
[0065] Step 2: Place the obtained silicon-magnesium alloy in a ball mill, add zirconium oxide ball milling beads as needed, use n-hexane as a grinding aid, ball mill at a speed of 400r / min for 4h, use ethanol as a dispersant for the ball-milled magnesium silicide powder, ultrasonically oscillate for 1h, centrifuge the obtained solution in a centrifuge at a speed of 400r / min, take the supernatant, and remove the precipitate with a larger particle size. Centrifuge the supernatant in a centrifuge at a speed of 700r / min, take the precipitate, remove the supernatant with a smaller particle size, and freeze-dry the precipitate for 12h to obtain magnesium silicide with a particle size of 3-5μm;
[0066] Step 3: The obtained Mg2Si powder is heated to 700°C at a heating rate of 5°C / min in an ammonia atmosphere and kept at this temperature for 6 hours to perform a nitridation reaction of magnesium silicide;
[0067] Step 4: The powder obtained after nitridation treatment was acid-washed with 1M / L HCl solution for 4 hours to remove Mg3N2 impurities, and then the solution was filtered to neutrality and freeze-dried for 12 hours to obtain silicon material.
[0068] Since the temperature of the nitridation reaction in this comparative example is low, the nitridation reaction is not sufficient and Mg2Si cannot be completely converted into Mg3N2 and Si. In the subsequent hydrochloric acid etching process, HCl will directly react with the unreacted Mg2Si, reacting most of the material to form a hollow structure, which is inconsistent with the original intention of material synthesis.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing high-purity porous silicon material from photovoltaic waste silicon, characterized in that: The following steps are involved: Step 1: reacting silicon powder crushed from photovoltaic waste silicon with magnesium powder to synthesize magnesium silicide; Step 2: Grinding magnesium silicide to obtain magnesium silicide powder; Step 3: subjecting the ground magnesium silicide powder to a nitridation reaction treatment; Step 4: The product obtained by the nitridation reaction is acid-washed, filtered, and dried to obtain a high-purity porous silicon material.
2. The method for preparing high-purity porous silicon material from photovoltaic waste silicon according to claim 1, characterized in that: In the step 1, the particle size of the silicon powder crushed from photovoltaic waste silicon is 1-10 μm, and the mass ratio of silicon powder to magnesium powder is 1:(1-2).
3. The method for preparing high-purity porous silicon material from photovoltaic waste silicon according to claim 1, characterized in that: In the step 1, the reaction conditions of the silicon powder and magnesium powder are heating to 550-600° C. in an atmosphere of protective gas and reacting for 4-6 hours.
4. The method for preparing high-purity porous silicon material from photovoltaic waste silicon according to claim 1, characterized in that: In the step 1, the heating rate is 2-10°C / min.
5. The method for preparing high-purity porous silicon material from photovoltaic waste silicon according to claim 1, characterized in that: In the step 2, the particle size of the ground magnesium silicide powder is 3-5 μm.
6. The method for preparing high-purity porous silicon material from photovoltaic waste silicon according to claim 1, characterized in that: In the step 2, the preparation method of the magnesium silicide powder is as follows: the magnesium silicide synthesized in the step 1 is placed in a ball mill, n-hexane is used as a grinding aid, 8-12 times the mass of zirconium oxide ball milling beads are added, and the ball milling is carried out at 300-500r / min for 3-5h; ethanol is used as a dispersant, ultrasonically oscillated for 0.5-2h, and then centrifuged at 300-500r / min for 5-10min to obtain the supernatant, the obtained supernatant is centrifuged at 600-800r / min for 5-10min, and the lower layer of precipitate is removed, and the precipitate is freeze-dried to obtain magnesium silicide powder.
7. The method for preparing high-purity porous silicon material from photovoltaic waste silicon according to claim 1, characterized in that: The nitridation reaction treatment in step 3 is to heat the ground magnesium silicide powder to 700-900° C. at a heating rate of 2-10° C. / min in an atmosphere containing ammonia and keep the temperature for 3-6 hours.
8. The method for preparing high-purity porous silicon material from photovoltaic waste silicon according to claim 1, characterized in that: The product obtained by the nitridation reaction treatment in step 4 is pickled with a 0.5-1.5M / L hydrochloric acid solution for 3-5 hours.
